Анализ процессов традиционного и плазменного плавления золы ТЭЦ; Техника и технология силикатов; Т. 23, № 3 - Волокитин О. Г. Олег Геннадьевич; Верещагин В. И. Владимир Иванович; Волокитин Г. Г. Геннадий Георгиевич; Скрипникова Н. К. Нелли Карповна; Шеховцов В. В. Валентин Валерьевич (2016, 2016)
Заглавие с экрана